Think for yourself restoring common sense in an age of experts & artificial intelligence - Vikram Mansharamani (Boston, MA Harvard Business Review Press, 2020)
"We've outsourced too much of our thinking. How do we get it back? At the height of the 2014 Ebola epidemic, a man who had recently returned from West Africa with a fever and severe abdominal pain entered a hospital in Dallas--and was sent home. Even after healthcare workers learned their patient had come from Liberia, ground zero of the Ebola hot zone, not one of those treating him considered the deadly virus as a possible cause of his condition. Shortly after the man died, one of the nurses who had treated him sought clearance from the Centers for Disease Control to board a commercial flight. She reported a fever of 99.5 degrees, but because the protocol restricted travel at 100.4 degrees or higher, she was cleared. She was later confirmed to be infected with Ebola. A public health disaster akin to the one depicted in the movie Contagion was averted, but only by sheer luck. How could this happen? As Harvard lecturer and global trend watcher Vikram Mansharamani shows in this eye-opening and perspective-shifting book, our complex, data-flooded world has made us ever more reliant on experts, protocols, and technology. We've stopped thinking for ourselves. (Have you ever followed your GPS device to a deserted parking lot?) With stark and compelling examples drawn from business, sports, and everyday life, the author illustrates how in a very real sense we have outsourced too much of our thinking, relinquishing our autonomy. Of course, experts, protocols, and computer-based systems are essential to helping us make informed decisions. What we need is a new approach for integrating these information sources more effectively, harnessing the value they provide without undermining our own autonomy. The author provides principles and techniques for doing just that, empowering readers with a more critical and nuanced approach to making decisions. Think for Yourself is an indispensable guide for those looking to restore self-reliant thinking in a data-driven and technology-dependent yet overwhelmingly uncertain world"-- Provided by publisher.
Includes index.
Keywords: Common sense